Synthesis of the adenovirus-coded DNA binding protein in infected cells. - Gilead, Z (1976)
Synthesis of the 75K (75K indicates a moleculatr weight of 70,000 to 75,000) DNA binding protein, an early virus-coded protein in adenovirus 2-infected KB cells, and its regulation were studied by using a radioimmune precipitation inhibition assay. The protein was first detected at 4 h postinfection and accumulated at an expoential rate. An arrest of further synthesis (accumulation) was observed at 10 to 11 h postinfection, coinciding with the onset of synthesis of late virion proteins. In contrast, when the infected cells were treated with 25 mug of arabinosyl cytosine per ml to block viral DNA replication, the synthesis of 75K protein did not cease but continue for up to 36 h postinfection. The synthesis of 75K protein in cells after release from a cycloheximide block (2 to 9 h postinfection) was analyzed. Increased amounts of early adenovirus-specific mRNA accumulate in infected cells during a cycloheximide block (Parsons and Green, 1971). However, cycloheximide treatment did not produce increased levels of 75K protein, and an abrupt arrest of 75K protein formation was again observed at the time of synthesis of late virion proteins. Partition of the 75K protein between the nuclear and cytoplasmic fractions during the course of infection was studied. The 75K protein appeared first in the cytoplasm and then in the nucleus after a slight lag. Accumulation of the 75K protein continued both in the cytoplasm and nucleus, with higher levels being found in the cytoplasm.